Usulan Perbaikan Fasilitas Kerja dengan Pendekatan Ergonomi pada UMKM Bani Marfu Farm - Ferdi Kurniawan; Kusnadi Kusnadi (Peneliti.net, 2022)
Musculoskeletal Disorders is a condition where there is a disorder that attacks the function of muscles and bones. MSDs often occur when the work facilities used during work do not apply ergonomic principles. MSME Bani Marfu Farm is a type of poultry farming business that has work facilities that do not apply ergonomic principles. The purpose of this research is to identify jobs that do not apply ergonomic principles, find out the complaints felt by workers, and design proposals for improving work facilities. The research methods used to assess work posture are the Rapid Entire Body Assessment, Workplace Ergonomic Risk Assessment, and Novel Ergonomic Postural Assessment methods. The method used to design work facilities is the Ergonomic Function Deployment method. The results showed that the work of cleaning livestock manure has a level of risk that can cause ongoing MSDs complaints. The proposed corrective action is to design a tool that can dispose of livestock manure automatically so as to improve work posture. The results of the analysis by paying attention to the value of Net Present Value, Payback Period, and Return of Investment indicate that the investment in the procurement of proposed work tools is said to be feasible.